Development, Evaluation, and Characterization of a Novel Mucoadhesive Film Containing Pterodon pubescens Benth Ethanolic Extract for Dental Use - Figueiredo, Mariana Cecchetto; Zanutto, Fabiana Volpe; Sabri, Akmal; Cândido, Tuany Zambroti; Medina, Leila Servat; de Oliveira Sousa, Ilza Maria; Basting, Rosanna Tarkany; de Oliveira Braga, Lucia Elaine; de Oliveira, Ellen Cristina Souza; de Feiria, Simone Nataly Busato; da Fonseca‐Santos, Bruno; Chorilli, Marlus [UNESP]; et al. (Wiley, 2025)
ABSTRACT Periodontal diseases involve infectious and inflammatory processes that affect oral tissues. Extracts from Pterodon pubescens Benth (sucupira) have demonstrated antinociceptive, anti‐inflammatory, anti‐edematogenic, and antiplatelet effects, highlighting their therapeutic potential for periodontal treatment. However, an effective pharmaceutical delivery system is necessary for targeted administration. This study aimed to develop and characterize a mucoadhesive oral film loaded with sucupira extract for dental applications. Films were prepared using polyvinyl alcohol (PVA) and characterized for nanoparticle size, mechanical properties, permeation, and cytotoxicity. Nanoparticles ranged from 200 to 500 nm with crystalline structures observed. Increased extract concentration enhanced zeta potential and reduced nanoparticle count with a polydispersity index of 0.5. Mechanical tests showed strong films with low mucoadhesive properties. Permeation studies indicated that films with 3% (w/w) extract released approximately 41% of methyl 6α‐acetoxy‐7β‐hydroxy‐vouacapan‐17β‐oate ester after 8 h, outperforming films with 1% extract. Cytotoxicity assays with human gingival fibroblasts (HGF‐1) revealed higher cell viability for the film‐incorporated extract compared to free extract. Furthermore, the sucupira extract loaded‐PVA film was able to mitigate the pro‐inflammatory pathway exhibited by reducing neutrophil infiltration. These findings suggest that the mucoadhesive film with 3% (w/w) P. pubescens extract is a promising candidate for the development of a new oral formulation for dental use.